Effectiveness of Cognitive-Based Mindfulness on Self-Compassion and Integrative Self-Knowledge in Individuals with Borderline Personality Disorder - Sadeghian Lemraski, Somayeh; Akbari, Hamzeh; Mirani, Arastoo (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Borderline personality disorder is a complex disorder associated with significant prevalence, mortality, and public health costs. The current study aimed to determine the effectiveness of cognitive-based mindfulness therapy on self-compassion and integrative self-knowledge in individuals with borderline personality disorder. Methods and Materials: The method of the present study was a quasi-experimental design with a pre-test-post-test and follow-up along with a control group. The statistical population of this research included all individuals with borderline personality disorder who were referred to the Nik Andish Sari Psychiatric Clinic in 2021-2022. Among them, 24 individuals who met the study entry criteria and scored high on the borderline personality disorder assessment were selected as the sample group and randomly assigned into two groups: experimental (12 people) and control (12 people). Data were collected using the Structured Clinical Interview for DSM Axis Disorders (First et al., 1995), the Self-Compassion Scale (Neff, 2003), and the Integrative Self-Knowledge Scale (Ghorbani et al., 2008). Data were analyzed using repeated measures analysis of variance and SPSS software. Findings: The results showed that cognitive-based mindfulness therapy was effective on self-compassion (F = 38.86, p < .001) and integrative self-knowledge (F = 15.25, p < .001). Moreover, these results indicated that there was a significant increase in self-compassion and integrative self-knowledge during the follow-up stage in the experimental group compared to the control group. Conclusion: It can be concluded that cognitive-based mindfulness therapy was effective in improving self-compassion and integrative self-knowledge in individuals with borderline personality disorder.